Metabolic Stress Impairs Pericyte Response to Optogenetic Stimulation in Pancreatic Islets - Michau, Aurélien; Lafont, Chrystel; Bargi-Souza, Paula; Kemkem, Yasmine; Guillou, Anne; Ravier, Magalie A.; Bertrand, Gyslaine; Varrault, Annie; Fiordelisio, Tatiana; Hodson, David J.; Mollard, Patrice; Schaeffer, Marie (Frontiers in Endocrinology, 2022)
Pancreatic islets are highly vascularized micro-organs ensuring whole body glucose homeostasis. Islet vascular cells play an integral part in sustaining adequate insulin release by beta cells. In particular, recent studies have demonstrated that islet pericytes regulate local blood flow velocity and are required for maintenance of beta cell maturity and function. In addition, increased metabolic demand accompanying obesity alters islet pericyte morphology. Here, we sought to explore the effects of metabolic stress on islet pericyte functional response to stimulation in a mouse model of type 2 diabetes, directly in the pancreas in vivo. We found that high fat diet induced islet pericyte hypertrophy without alterations in basal local blood flow. However, optogenetic stimulation of pericyte activity revealed impaired islet vascular responses, despite increased expression of genes encoding proteins directly or indirectly involved in cell contraction. These findings suggest that metabolic stress impinges upon islet pericyte function, which may contribute to beta cell failure during T2D.